Speech By Kol. Prof. Dato’ Dr. Kamarudin Hussin, Universiti Malaysia Perlis (UniMAP) Vice Chancellor, Certificate Ceremony For UniMAP-Industry Dinner - Kamarudin Hussin, Kol. Prof. Dato’ Dr. (2009)
Ceremony at Dewan Tabung Haji, Penang